NOD-like receptors in pathogenesis of missed and spontaneous abortions - O. P. Lebedeva; V. M. Ivannikova; I. O. Zhukova; O. N. Kozarenko; O. B. Altukhova; S. P. Pakhomov; M. I. Churnosov (Акушерство, гинекология и репродукция)
Nucleotide-binding oligomerization domain-like receptors (NOD-like receptors) are cytosolic signaling receptors of innate immune cells recognizing ligands derived from bacteria, viruses, fungi and protozoa. They can initiate apoptosis and pro-inflammatory cytokines production. Meanwhile, the role of decidual NOD-like receptors in pathogenesis of early miscarriages remains unknown. Aim: to study NOD-like receptor (NOD1, NOD2, NLRP1, NLRP3, NLRC4) messenger ribonucleic acid (mRNA) expression in decidual tissue from patients with missedand spontaneous abortions compared to progressive pregnancy.Materials and Methods. NOD1, NOD2, NLRP1, NLRP3, NLRC4 and pathway protein receptorinteracting-serine/threonine-protein kinase 2 (RIP-2) mRNA expression in decidua from 34 patients with missed abortions (group I), 34 patients with spontaneous abortions (group II) and 57 women with progressive pregnancy admitted for artificial abortion (group III, control group) were analyzed by reverse transcription quantitative polymerase chain reaction (PCR) at gestational age of 6–10 weeks. Exclusion criteria were as follows: endocrine disorders, severe extragenital diseases, antiphospholipid syndrome, inherited thrombophilia, uterine malformations and fetal chromosomal abnormalities. Samples were collected by uterine abrasion. Results. It was found that mRNA expression of NOD2 was significantly higher in decidua from patients with missed and spontaneous abortions, whereas for RIP-2 (related to relevant signaling pathway) – in women with missed abortions. A moderate positive correlation between gestational age and mRNA expression for NOD2 (R = 0.48; p = 0.01) and RIP-2 (R = 0.41; p = 0.007) was observed in subjects with progressive pregnancy. In contrast, women with missed abortions showed a moderate negative correlation between body weight and mRNA expression for NOD2 (R = –0.46; p = 0.03) and RIP-2 (R = –0.51; p = 0.02) whereas spontaneous abortions was associated with moderate negative correlation between RIP-2 mRNA expression and body weight (R= –0.47; p=0.04) as well as body mass index (R= –0.48; p = 0.04) along with moderate positive correlation with age of menarche (R = 0.46; p = 0.04). However, compared with progressive pregnancy no significant differences were found in expression level form NOD1, NLRP1, NLRP3 and NLRC4 mRNA in decidua from patients with missed and spontaneous abortions. Conclusion. Elevated NOD2 mRNA expression was observed in decidua from patients with missed and spontaneous abortions compared to progressive pregnancy paralleled with upregulated RIP-2 mRNA expression in missed abortions. Finally, it was found that NOD1, NLRP1, NLRP3 and NLRC4 were not involved in pathogenesis of miscarriages.